The Effect of Road Network on the Analysis Result of the Level of Degraded Land (The Case at Tanjung Aur Watershed, Bengkulu Province) - Bambang Sulistyo (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2018)
This study aims to investigate the effect of the road network on the results of the analysis of the level of degraded land at Tanjung Aur watershed, Bengkulu Province.The research method involves digital analysis of all the data affecting erosion and degraded land. The level of degraded land is defined as (Erosion + Slope + Percentage of Canopy Cover + Management), whereas the erosion itself is determined by the Universal Soil Loss Equation model and formulated as A = R x K x LS x C x P. All parameters are collected and then performed the analysis to produce as a map of the level of degraded land. Prior to the calculation of erosion and the level of degraded land, it is first made a map of land units which is the result of overlay analysis among land erodibility, slope and land use maps.In the first phase analysis, the calculation of erosion and the level of degraded land is done prior to the inclusion of road network, while in the second phase, calculation are done after the inclusion of road network. The results of the two analyzes are then compared to determine the effect of the inclusion of road network on the results of the analysis of the level of degraded land, either on the effect on the category changes in the level of degraded land and its coverage.The results showed that there were 690.42 hectares (4.7%) of the study area (14,684.86 hectares) whose the level of degraded land was changed as a result of the inclusion of road network, from the level of